(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the clinical characteristics and imaging characteristics of children with Moyamoya disease at the Central Children’s Hospital in 2017-2023. Research subjects and methods: The study describes a series of retrospective and prospective cases on 51 pediatric patients at the Central Children’s Hospital selected by convenience sampling method. Analyze and process data using STATA software. Results: The proportion of pediatric patients with a Glasgow score of 15 points accounted for 60.8%, and clinical symptoms of focal paralysis accounted for the highest proportion, up to 82.3%. Evaluation of Rankin score at the time of admission showed that the proportion of pediatric patients with score 4 was quite high, reaching 62.7%. Among cases diagnosed with Moyamoya disease on admission, stroke accounts for the largest proportion, up to 43,1%, and 94.1% of these show stenosis or occlusion of the middle cerebral artery. Conclusion: Moyamoya disease can present with transient neurological symptoms accompanying strokes and is often missed, leading to late diagnosis. Although Moyamoya disease is uncommon, the disease burden remains heavy due to high hospitalization rates, long hospital stays, and rising costs. Moyamoya should be considered and diagnostic evaluation should be initiated in patients, especially children, who present with acute neurological deterioration or unexplained symptoms related to cerebral ischemia local.